ANALISIS KEBUTUHAN DIKLAT JABATAN WAKIL KEPALA SEKOLAH BIDANG KURIKULUM SD NEGERI DI LINGKUNGAN SUKU DINAS PENDIDIKAN JAKARTA PUSAT II - Nacep Hamrat, - (2021)
The assistant principal in curriculum affairs is a strategic position, so it is necessary to carry out training for these office holders to carry out their roles properly. For training to run well, it needs to be preceded by implementing a training needs analysis. The study aims to analyze the training's need for an assistant principal in public elementary school curriculum affairs. The questions posed in the research were 1) What is the assistant principal's competency profile in the curriculum affairs?; 2) Are there differences in the assistant principal's competency mastery in the curriculum affairs based on the educational background?; 3) What are the compulsory training that needs to be developed to improve the performance of assistant principals in curriculum affairs?; 4) What optional training needs to be developed to strengthen assistant principals' performance in curriculum affairs?. The research method used was a mixed-method, with univariate statistical analysis techniques. This study population consisted of 68 assistant principals in the curriculum affairs, with a sample of 58 respondents. Research respondents came from Cempaka Putih, Johar Baru, Senen, and Kemayoran. The results of the research were: 1) The assistant principal still needs strengthening of the competence in the field of duties related to curriculum development; 2) There is a significant difference between the educational background of the respondent and the competence they have; 3) Compulsory training that needs to be developed for all assistant principals in curriculum affairs is curriculum development competency; 4) Optional training that needs to be developed for assistant principals in curriculum affairs is student management training, personnel, finance, infrastructure, and information technology training. Research is expected to provide input for the Ministry of Education, Culture, Research, and Technology to include curriculum development competencies as the competence of assistant principals in curriculum affairs. Moreover, The research is expected to provide input for developing the assistant principal's training in curriculum affairs.